ANALYSIS OF THE CURRENT STATE OF CYBERATTACKS IN UKRAINE DURING THE WAR - Khramov , Sviatoslav; Opirskyy, Ivan (Ukrainian Information Security Research Journal, 2024)
The urgency of the cybersecurity problem in Ukraine is extremely high in the context of a full-scale invasion. In recent years, cyberattacks have become an integral part of the hybrid war waged against the country. The study of the current state of cyber aggression in Ukraine is an important task from the point of view of national security. This scientific work aims to carefully analyze the structure, trends, and features of cyberattacks against Ukraine during the military conflict. The study involves the analysis of various forms and methods of cyber aggression, studying their impact on the state, and identifying possible measures to protect critical information infrastructure facilities. The study's results can form the basis for the development and implementation of effective cybersecurity strategies aimed at improving the protection of the country's information security in conditions of war. The relevance of this work lies in its potential to help the Ukrainian government and security agencies effectively respond to the challenges of military conflict in cyberspace. To support the study, a broad analysis of the literature and articles providing information on cyber attacks during the war was conducted. Additionally, empirical data on cyber incidents recorded in Ukraine since the beginning of the conflict were used to comprehensively assess the scope and specifics of the threats. Special attention is paid to the analysis of types of cyberattacks, their tactical and strategic objectives, and the methods used for their implementation. The study also identifies key vulnerabilities exploited by attackers and suggests possible ways to mitigate them. The main types of attacks considered include DDoS attacks, phishing attacks, malware deployment, SQL injections, and others. Moreover, the impact of cyberattacks on various sectors of the economy and social sphere, including government administration, energy, finance, and infrastructure, is examined. The results of the study are practically significant for shaping national cybersecurity policy. They can be used to develop recommendations for enhancing the security of information systems, improving the regulatory framework, and strengthening international cooperation in this field. The study also emphasizes the need to increase cyber hygiene among the population and improve the training of cybersecurity specialists.